2020
DOI: 10.1002/ijgo.13523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postpartum dyspareunia: A systematic review and meta‐analysis

Abstract: Background Dyspareunia is one of the most common postpartum sexual dysfunctions. Objective To estimate the prevalence of postpartum dyspareunia. Search strategy Web of Science, Scopus, PubMed, and Embase databases were searched to July 2019 using keywords including ‘perineal pain,’ ‘dyspareunia,’ and ‘sexual pain’. Selection criteria Observational studies on the prevalence of postpartum dyspareunia were included. Data collection and analysis Two authors independently reviewed articles and extracted data. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
3
27
0
2
Order By: Relevance
“…Consistent with a systemic review 34 that reported the prevalence of dyspareunia as 43% at 2-6 months postpartum and 22% at 6-12 months postpartum, 34.7% of the primiparous women had dyspareunia in the present study. The type of delivery, episiotomy, perineal lacerations, lactation, and depression have been regarded as risk factors for dyspareunia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with a systemic review 34 that reported the prevalence of dyspareunia as 43% at 2-6 months postpartum and 22% at 6-12 months postpartum, 34.7% of the primiparous women had dyspareunia in the present study. The type of delivery, episiotomy, perineal lacerations, lactation, and depression have been regarded as risk factors for dyspareunia.…”
Section: Discussionsupporting
confidence: 92%
“…The type of delivery, episiotomy, perineal lacerations, lactation, and depression have been regarded as risk factors for dyspareunia. 34 , 35 Several studies have investigated the effect of perineal tears and episiotomy on dyspareunia and concluded that the incidence of dyspareunia develops with progressive perineal tears and episiotomy. 35 , 36 Moreover, perineal lacerations and episiotomy were found to be associated with a longer second stage of labor duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hage‐Fransen and colleagues examined factors associated with pelvic floor disorders of UI, anal incontinence, and pelvic prolapse postpartum, both short‐term (<18 months) and long‐term (2‐12 years) 1 . Banaei and colleagues examined the rate of dyspareunia postpartum 2 . Batmani et al estimated the worldwide prevalence of UI in older women 3 .…”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 99%
“…Dyspareunia can be affected by not only psychosocial factors but also hormonal changes, which are extensive during the childbearing cycle, and genital tract trauma during birth. Banaei and colleagues’ meta‐analysis included 22 cross‐sectional and cohort studies that examined rates between 2 and 24 months postpartum 2 . The sample sizes ranged from 78 to 2413 for a total of nearly 11,500 participants.…”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 99%